2017
DOI: 10.5301/hipint.5000468
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Reaction to Metal Debris in a Consecutive Series of DUROM™ Hip Resurfacing: Pseudotumour Incidence and Metal Ion Concentration

Abstract: A significant proportion of patients developed pseudotumours and metal ion elevation in a consecutive cohort of DUROM™ HRA after mid-term follow-up. The incidence, however, seems not to differ from results of other well performing resurfacing brands; clinical relevance of our findings is unclear. Regarding potential local as well as systemic effects of metal particle release, close follow-up of patients is essential, even with clinically well-performing implants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 30 publications
0
4
0
1
Order By: Relevance
“…It was observed that all arthroplasties, including TKA, expose the patient to released metal ions [ 11 ]. Exposure to metal ions may lead to an ALTR which has been primarily linked with MoM bearings in THA [ 7 ]. After TKA, ALTR is a rare condition, and the formation of large soft-tissue masses has only rarely been described in this context.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was observed that all arthroplasties, including TKA, expose the patient to released metal ions [ 11 ]. Exposure to metal ions may lead to an ALTR which has been primarily linked with MoM bearings in THA [ 7 ]. After TKA, ALTR is a rare condition, and the formation of large soft-tissue masses has only rarely been described in this context.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that ALTR may lead to soft-tissue mass, or formerly described as pseudotumor, formation [7]. These fluid-filled or solid soft-tissue lesions result from an innate and adaptive immune response secondary to wear, particle toxicity, and host immunological hypersensitivity or allergy [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…However, other possible effects of the coating, such as an impact on aseptic loosening or PRO, would also be assessed in a non-allergic population. Metal ion concentrations were measured in the blood only, and the local reaction in the joint might be different, as there is no good correlation between blood levels and adverse reaction to metal debris (ARMD) in MoM hip arthroplasties [41] and there are no such studies in TKA. Metal ion concentrations were below the detection limits in many patients; nevertheless, values below 2 µg/l, which is far above the detection limit, are considered to be safe and, therefore, concentrations which might be relevant for patients were detected.…”
Section: Discussionmentioning
confidence: 99%
“…Ein Rückschluss auf die lokale Reaktion im Gelenk ist damit nicht sicher möglich. Aus Studien zu den MoM-Gleitpaarungen in der Hüftendoprothetik ist bekannt, dass kein ausreichender Zusammenhang zwischen den Blutwerten und einer lokalen adversen Gewebsreaktion ("adverse reactions to metal debris") besteht [14]. Ähnliche Studien in der Knieendoprothetik existieren nicht.…”
Section: Limitationenunclassified